Treatment of paroxysmal supraventricular tachycardia with intravenous injection of adenosine triphosphate. Issue 3 (March 1986) - Saito, D; Ueeda, M; Abe, Y; Tani, H; Nakatsu, T; Yoshida, H; Haraoka, S; Nagashima, H
Abstract : Intravenous adenosine triphosphate rapidly terminated all 11 episodes of paroxysmal supraventricular tachycardia in 10 patients. Eight patients reported side effects but these resolved within 20 seconds and did not require treatment. Adenosine triphosphate is a suitable agent for the rapid termination of paroxysmal supraventricular tachycardia.